Arsenic in the Environment: Bridging Science to Practice for Sustainable Development As2021: Proceedings of the 8th International Congress and Exhibition on Arsenic in the Environment (As2021), June 7-9, 2021, Wageningen, The Netherlands - Albert Van der Wal; Arslan Ahmad; Branislav Petrusevski; Jan Weijma; Dragan Savic; Patrick van der Wens; Erwin Beerendonk; Prosun Bhattacharya; Jochen Bundschuh; Ravi Naidu (CRC Press, 2023)
The Congress and Exhibition Series ""Arsenic in the Environment"" offers an international, multi- and interdisciplinary discussion platform for research and innovation aimed towards a holistic solution to the challenges posed by the environmental toxin arsenic, with global societal impact. The Congress has focused on cutting edge and breakthrough research in physical, chemical, toxicological, medical, agricultural and other specific issues on arsenic across a broader environmental realm. The Biennial Congress and Exhibition ""Arsenic in the Environment"" was first organized in Mexico City (As2006) followed by As2008 in Valencia (Spain), As2010 in Tainan (Chinese Taiwan), As2012 in Cairns (Australia), As2014 in Buenos Aires (Argentina), As2016 in Stockholm (Sweden) and As2018 in Beijing (P.R. China). The 8th International Congress As2020 was held June 7-9, 2021 (first time digitally owing to the global COVID-19 pandemic, in Wageningen, The Netherlands) and with a title Arsenic in the Environment - Bridging Science to Practice for Sustainable Development. The Congress addressed the broader context of arsenic research aligned on the following themes: Theme 1: Arsenic in Natural Soil and Water Systems Theme 2: Arsenic in Agriculture and Food Production Theme 3: Health Impacts of Arsenic Theme 4: Technologies for Arsenic Removal from Water Theme 5: Sustainable Mitigation and Management for Sustainable Development Arsenic in drinking water and food is a major health issue, affecting millions of people in many parts of the world. In recent years serious cases of arsenic exposure through different environmental matrices have been reported from, for example, Argentina, Bangladesh, Chile, China, Taiwan, Turkey, India, Mexico, UK, USA, Pakistan, Vietnam as well as other regions in the world. Arsenic can cause a number of carcinogenic and non-carcinogenic adverse effects on human health and therefore human exposure to arsenic should be avoided. Notably, The Netherlands has been in the forefront of research on arsenic removal technology and developed a cutting edge innovation to remove arsenic to levels below the WHO drinking water guideline to as low as less than 1 μg/L. This has created an enabling environment to discuss on policy issues for defining the new drinking water guideline. The Congress has attracted professionals involved in different segments of interdisciplinary research on arsenic in an open forum, and strengthened relations between academia, research institutions, government and non-governmental agencies, industries, and civil society organizations to share an optimal ambience for exchange of knowledge.
Keywords: 360; Environmental toxicology; Arsenic; Health impact; Arsenic removal; Sustainable development